Mechanical behavior of carbon fibers polyphenylene sulfide composites exposed to radiant heat flux and constant compressive force. (15th September 2018) - Carpier, Y.; Vieille, B.; Maaroufi, M.A.; Coppalle, A.; Barbe, F.
Abstract: The thermo-mechanical behavior of carbon/PPS laminates under a constant compressive stress and radiant heat flux has been studied in the case of a quasi-isotropic layup. Though lots of studies focus on the time-to-failure, the present work is aimed at investigating the influence of thermal and mechanisms phenomena on the fire behavior of composite structures. The mechanical response is studied at different scales. From the total macroscopic strain standpoint, the response is divided into three stages, referred to as transient, stationary and failure stages. During these stages, different thermal and mechanical mechanisms compete and prevail depending on the applied compressive stress: thermal and thermo-chemical expansion, decomposition, changes in the mechanical properties, etc. With the measurement of macroscopic thermal strains, the mechanical strain is calculated, enabling the calculation of a macroscopic damage factor describing only the mechanical phenomena. Other quantitative indicators are also used to study the competition between thermally- and mechanically-induced mechanisms: maximal expansion, strain rate, etc. It is shown that under a low compressive force, the thermal expansion is a strain-driven mechanism. Failure is studied at the meso scale. The formation and development of porosities associated with the transition liquid-gas (due to the PPS matrix decomposition) leads to micro-buckling in matrix-rich areas and ultimately, to the formation and propagation in the transverse direction of plastic kink bands. Post-failure observations show that this macroscopic kinking propagates specifically according to the decomposition state of the material.